A magyar államtér változásainak történeti és politikai földrajzi szemlélete a magyar földrajztudományban 1948-ig - Hajdú, Zoltán (Tér és Társadalom, 1995)
The territory of the Hungarian state changed and rearranged very many times during history. Until 1526 the active (in some directions conquering) role of the Hungarian state was a dominant content of the changes, Hungary reached the status of a regional power in Central Europe. Following 1526 Hungary became a buffer region between the great powers, after 1710 it was part of the Habsburg Empire, with a relative independence. After 1867 the inner state structure of the Austro-Hungarian Monarchy was provided by the Constitution. The 20th century brought frequent and radical transitions in the territory of the state. Modern Hungarian geography, from its birth, paid great attention to the researches of the historical problems of the state territory. The notion of the historical "Hungarian Empire" and the imperial role had significant everyday political relevance. The awareness of the imperial past organically integrated into Hungarian geography, in broader sense into the Hungarian public thinking. Following the fall in 1918 and the Trianon Treaty in 1920, the whole of Hungarian geography was claiming territorial revision. The historical territory of the Hungarian state and the historical Hungarian spirit were given everyday political content. Between 1945-1948 a kind of self-correction occurred in the Hungarian geography, which could mainly be seen in the change of style. Historically, however, it could not fully develop, due to the political and systemic change of 1949.